2014
DOI: 10.1016/j.bbamcr.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and chemokines: At the crossroads of cell signalling and inflammatory disease

Abstract: Inflammation occurs as a result of exposure of tissues and organs to harmful stimuli such as microbial pathogens, irritants, or toxic cellular components. The primary physical manifestations of inflammation are redness, swelling, heat, pain, and loss of function to the affected area. These processes involve the major cells of the immune system, including monocytes, macrophages, neutrophils, basophils, dendritic cells, mast cells, T-cells, and B-cells. However, examination of a range of inflammatory lesions dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
1,349
1
40

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,726 publications
(1,418 citation statements)
references
References 287 publications
28
1,349
1
40
Order By: Relevance
“…Chemokines are low molecular weight cytokines primarily responsible for chemotaxis of either specific leucocytes or groups of leucocytes [7]. CXCL10, along with the closely related chemokines CXCL9 and CXCL11, is an interferon (IFN)-g-inducible agonist for the CXCR3 chemokine receptor, which is rapidly induced on naive T cells following activation, and remains highly expressed by Th1 CD4…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines are low molecular weight cytokines primarily responsible for chemotaxis of either specific leucocytes or groups of leucocytes [7]. CXCL10, along with the closely related chemokines CXCL9 and CXCL11, is an interferon (IFN)-g-inducible agonist for the CXCR3 chemokine receptor, which is rapidly induced on naive T cells following activation, and remains highly expressed by Th1 CD4…”
Section: Introductionmentioning
confidence: 99%
“…Cells of the innate immune system including monocytes/macrophages, mast cells, and neutrophils play critical roles in infarct healing through tissue phagocytosis and activation of reparative responses. Recruitment and trafficking of these leukocytes to the heart following acute injury occur through the action of chemokines on their receptors to promote their migration to the site of injury (2), and have been the focus of much research in recent years (1,3).…”
mentioning
confidence: 99%
“…Since then, researchers have identified more than 300 cytokines (ILs, IFNs, TNFs, growth factors and chemokines) (Turner et al, 2014). These extracellular molecules are primarily produced to support the functions of the immune cells, and trafficking and communication between them, but also with and between somatic cells (from Greek, cyto-, cell and -kinos, movement), in health as well as during pathological processes.…”
Section: Immune-to-brain Signalingmentioning
confidence: 99%
“…It is well-known that low doses of IL-1β are enough to induce specific responses. On a cellular level, it was shown that as few as 2% of all IL-1R1 need to be activated to induce an effect (Arend, 2002;Dinarello et al, 2012;Garlanda et al, 2013;Sims and Smith, 2010;Turner et al, 2014).…”
Section: Interleukin-1mentioning
confidence: 99%
See 1 more Smart Citation